Elaboration and Characterization of Poly(4‐vinylpyridine‐co‐N, N dimethylacrylamide)/Poly(styrene‐co‐methacrylic acid) Interpolymer Complexes. Issue 1 (February 2014) - Lassoued, Abdelghani; Djadoun, Saïd; Bulavin, Leonid; Guenet, Jean‐Michel
Summary Proton‐donor poly(styrene‐co‐methacrylic acid) containing 8 mol % of methacrylic acid (PSMA8) and poly(N, N‐dimethylacrylamide‐co‐4vinylpyridine) containing 20 mol % of 4‐vinylpyridine (PDMA4VP20) containing two proton accepting sites of different strength were synthesized and characterized by different techniques. By simply mixing appropriate amounts of these copolymers in chloroform, interpolymer complexes were formed, while homogeneous phases were observed when PSMA8 was mixed to poly(N, N‐dimethyl acrylamide) or poly(4‐vinylpyridine) in the same solvent. Due to the presence of specific interactions that occurred between the copolymers, these interpolymer complexes exhibited a single Tg in the whole composition range, higher than those calculated from the weight average values of the pure copolymers. The Tg‐composition curves of these three systems, analyzed using Brostow et al. (BCKV) equation, confirmed from the high a0 values, obtained with PSMA8/PDMA4VP20 that the presence of 4VP units in PDMA4VP copolymers increased the average strength of intermolecular hydrogen bonding in the PDMA4VP20/PSMA8 systems compared to PDMA/PSMA8 or PSMA8/P4VP blends due to a higher number and stronger efficient specific interactions. Competing specific interactions of different strength carboxyl‐pyridine, carboxyl‐amide and carboxyl‐carboxyl that occurred within these systems were evidenced by FTIR spectroscopy.